The O(1S) dayglow emission as observed by the WIND imaging interferometer on the UARS - B. H. Solheim; G. G. Shepherd; I. C. McDade; V. Singh; W. E. Ward (Annales Geophysicae)
Volume emission rate profiles of the O(1D-1S) 5577 Å dayglow measured by the WIND imaging interferometer on the Upper Atmosphere Research Satellite are analyzed to examine the O(1S) excitation mechanisms in the sunlit lower thermosphere and upper mesosphere. The observed emission profiles are compared with theoretical profiles calculated using a model which takes into account all of the known daytime sources of O(1S). These include photoelectron impact on atomic oxygen, dissociative recombination of O+2, photodissociation of molecular oxygen, energy transfer from metastable N2(A3Σ+u) and three body recombination of atomic oxygen. Throughout most of the thermosphere the measured and modelled emission rates are in reasonably good agreement, given the limitations of the model, but in the region below 100 km, where the oxygen atom recombination source is likely to dominate, the measured emission rates are considerably larger than those modelled using the MSIS-90 oxygen atom densities. This discrepancy is discussed in terms of possible inadequacies in the MSIS-90 model atmosphere and/or additional sources of O(1S) at low altitude.